The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsomega.2c00034
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Space–Time Synergy of Coal and Gas Co-mining

Abstract: The co-mining of coal and gas is the inevitable future direction of the mining of coal resources. Taking coal mining and gas extraction as the two subsystems of the coal and gas co-mining system, to reveal the mechanism of action between coal mining and gas extraction is the premise of orderly co-mining. On the basis of a similar simulation experiment of coal and gas co-mining, by obtaining the gas migration law during the mining process and collecting a large amount of data on the coal production and gas extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Proceeding from the experience of practical working in mine conditions allows for concluding that the quality of the normative forecast turned out to remain low. In most scientific works, two-dimensional curves or their aggregates in the form of projections on a two-dimensional plane are mainly considered [70][71][72][73]. For example, a two-dimensional curve characterized by the relationship between the methane concentration and distance S at different times, as well as the methane concentration change over time at different positions, is insufficiently representative (see Figure 2 in [26]) owing to the deformation of a three-dimensional surface when it is projected onto a two-dimensional plane.…”
Section: Methodsmentioning
confidence: 99%
“…Proceeding from the experience of practical working in mine conditions allows for concluding that the quality of the normative forecast turned out to remain low. In most scientific works, two-dimensional curves or their aggregates in the form of projections on a two-dimensional plane are mainly considered [70][71][72][73]. For example, a two-dimensional curve characterized by the relationship between the methane concentration and distance S at different times, as well as the methane concentration change over time at different positions, is insufficiently representative (see Figure 2 in [26]) owing to the deformation of a three-dimensional surface when it is projected onto a two-dimensional plane.…”
Section: Methodsmentioning
confidence: 99%
“…where c s is the volume fraction of component s; D s is the diffusion coefficient, m 2 /s; and S s is the mass of the component produced by the chemical reaction per unit time, kg/(m 3 •s). 4 Considered the extraction area as a porous medium and add momentum sources, which included viscous loss term and inertial loss term.…”
Section: Boundary Conditions and Parameter Settingmentioning
confidence: 99%
“…This led to frequent gas overrun problems in the return airway and upper corner. It hindered the safety production of the mine [3][4][5]. The concentration of gas extracted during coal mine production is less than 30%.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with the increase in coal mining depth and mining intensity, in the process of coal mining, the gas in adjacent layers or surrounding rock enters the work plane through mining fissures. The gas in the upper corner of the work plane easily causes the gas concentration in the return air flow to exceed the limit, which affects the safe mining of the work plane [8,9]. Former research has shown that a rock drainage roadway and high-level directional extraction borehole can effectively extract gas in the fissure zone and have great operational stability in the upper corner of the goaf and return air flow [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%